1993
DOI: 10.1029/93gl01399
|View full text |Cite
|
Sign up to set email alerts
|

Large massive sulfide deposits in a newly discovered active hydrothermal system, The High‐Rise Field, Endeavour Segment, Juan De Fuca Ridge

Abstract: Submersible observations and side‐scan sonar imagery delineate ten large venting sulfide‐sulfate‐silica structures located on an uplifted block of the axial valley floor on the central portion of the Endeavour Segment, Juan de Fuca Ridge. This newly discovered vent field lies 1.8 km north of the main Endeavour vent field. The axial valley, a horst, and faults controlling sulfide deposition trend parallel to the ridge axis. The horst rises 10 to 15 m above the valley floor and offsets a lava lake which extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 7 publications
0
95
0
Order By: Relevance
“…The High Rise vent field (47°58.00' N, 129°05.50' W) was discovered during reconnaissance dives to the north of the Main Endeavour field in 1988 and mapped in 1991 (Robigou et al 1993). The vent field is situated on a central horst within the narrow axial valley of the Endeavour Segment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The High Rise vent field (47°58.00' N, 129°05.50' W) was discovered during reconnaissance dives to the north of the Main Endeavour field in 1988 and mapped in 1991 (Robigou et al 1993). The vent field is situated on a central horst within the narrow axial valley of the Endeavour Segment.…”
Section: Methodsmentioning
confidence: 99%
“…2). Robigou et al 1993) McHugh (1989) examined the reproductive development of Paralvinella palmiformis in 3 samples collected from the Endeavour segment in July, August and September 1984. Very few or no oocytes were found in females from the samples collected in August and September, but oocytes were present in females from the July sample.…”
Section: Abstract: Hydrothermal Vents · Reproductive Development · Smentioning
confidence: 99%
“…The sulfide edifices at Endeavour are typically steepsided, often reaching heights of greater than 20 metres above the seafloor, with fluid venting temperatures that range from <10°C up to $375°C (Delaney et al, 1992;Robigou et al, 1993;Butterfield et al, 1994;Glickson et al, 2006;Kelley et al, 2012). The edifices are rich in barite relative to typical mid-ocean ridge deposits.…”
Section: Geological Settingmentioning
confidence: 99%
“…S&M has been the focus of an extensive biological and geological study, where the distnbution of fluid flow, geological features and 6 identified faunal assemblages (I to VI) were mapped and followed over a 4 yr penod (1991, 1994 & 1995) (Sarrazin et al 1997). Salut is a smaller, highly active edifice with abundant horizontal flanges that are typical of sulfide structures on Endeavour Segment (Delaney et al 1992, Robigou et al 1993, Hannington et al 1995. Sample collection.…”
Section: Studymentioning
confidence: 99%